Water gas shift reaction catalyst
By developing a catalyst composition containing zinc, aluminum, oxygen, and promoters, the toxic problems of chromium in existing catalysts and reducing the reducing problems during low steam and gas are achieved. Catalytic water gas transformation reaction.
Patent Information
- Application Number
- CN202380042612.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-24
AI Technical Summary
The existing water-gas transformation reaction catalysts contain toxic chromium, and they are easily reduced when operating at a low steam to gas ratio, resulting in hydrocarbon by-products.
A catalyst composition, including zinc, aluminum, oxygen, and promoters, such as cymbal, magnesium, copper, cobalt, iron, etc., and prepared through the pre -system of the spinel spinel to form materials with high crystal spinels.
The catalyst composition is basically no chromium, which can run within the range of wider steam and gas, and shows the activity that is quite or higher than the conventional iron/chromium catalyst.
Smart Images

Figure CN119365258A_ABST
Abstract
Description
Public background Public domain
[0002] The present disclosure relates generally to water-gas shift reaction catalyst materials. More specifically, the present disclosure relates to spinel-containing catalysts useful in high temperature water-gas shift reactions, to methods of making such catalysts, and to methods of forming hydrogen with such catalysts. Technical Background
[0003] The water gas shift reaction is a well-known reaction by which hydrogen is formed from water vapor and carbon monoxide. Many important chemical reactions require large amounts of hydrogen. Since the 1940s, the water gas shift reaction has represented an important step in the industrial production of hydrogen. For example, industrial-scale water gas shift reactions are used to increase the production of hydrogen for refinery hydrogenation processes and for the production of commodity chemicals such as ammonia, methanol, and alternative hydrocarbon fuels.
[0004] Conventionally, catalysts used for industrial-scale water-gas shift reactions include either an iron-chromium metal combination or a copper-zinc metal combination. Iron-chromium oxide catalysts are typically used in high temperature shift (HTS) converters, which typically have a reactor inlet temperature of about 300° C. to about 380° C. Conventional HTS converters use iron-based catalysts. Conventional catalysts are typically supplied in the form of pellets containing 8%-12% Cr2O3 and a small amount of copper as an activity and selectivity enhancer.
[0005] However, chromium can be toxic and carcinogenic and is therefore highly undesirable for use on an industrial scale due to health and environmental concerns. In addition, iron-containing HTS catalysts can only operate over a limited range of steam to gas ratios (S / G; i.e., the molar ratio of H2O to the sum of H2, N2, CO2, and CO) because at low S / G, the catalyst is reduced to iron carbides that produce hydrocarbon byproducts.
[0006] Therefore, there remains a need for water-gas shift reaction catalysts that can be prepared without chromium and optionally without iron without significantly affecting performance. In addition, there is a need for water-gas shift reaction catalysts that can operate over a wider S / G range than conventional catalysts can tolerate.
[0007] Public content overview
[0008] One aspect of the present disclosure is a water-gas shift reaction catalyst composition comprising:
[0009] zinc, present in the composition in an amount ranging from 20% to 70% by weight;
[0010] aluminum, present in the composition in an amount ranging from 5 wt % to 40 wt %;
[0011] one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, the one or more promoters being present in the composition in a total amount ranging from 0.1 wt % to 25 wt %; and
[0012] Oxygen is present in the composition in an amount ranging from 15 wt % to 50 wt %.
[0013] Such materials can be made to have a high degree of material in the crystalline spinel form, as described in detail herein.
[0014] Another aspect of the present disclosure is a method of preparing a water-gas shift reaction catalyst composition (e.g., according to the embodiments described herein), the method comprising:
[0015] providing a spinel precursor comprising zinc; aluminum; one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon; and oxygen; and
[0016] Calcination of spinel precursor,
[0017] The catalyst composition comprises:
[0018] zinc, present in the composition in an amount ranging from 20% to 70% by weight;
[0019] aluminum, present in the composition in an amount ranging from 5 wt % to 40 wt %;
[0020] one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, each promoter being present in the composition in an amount ranging from 0.1 wt % to 25 wt %; and
[0021] Oxygen is present in the composition in an amount ranging from 15 wt % to 50 wt % (eg, as further described in any of the embodiments herein).
[0022] Another embodiment of the present disclosure is a method of performing a water gas shift reaction comprising contacting a feed comprising water and carbon monoxide with a catalyst composition described herein to form hydrogen and carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a graph of X-ray diffraction (XRD) patterns of certain materials described herein.
[0024] Figure 2 is a graph of XRD patterns for certain materials described herein.
[0025] Detailed Description
[0026] The present disclosure relates to a calcined water-gas shift reaction catalyst composition comprising zinc, aluminum, oxygen and one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon. In various advantageous aspects and embodiments of the composition described herein, zinc, aluminum, oxygen and / or one or more promoters together form a spinel crystal structure. The disclosure indicates that such a catalyst, which may advantageously be substantially free of chromium, may exhibit activity comparable to or higher than that of a conventional iron / chromium catalyst. The disclosure indicates that such a catalyst may, in certain embodiments, be free of iron-containing materials and therefore operate over a wider range of steam to gas (S / G) ratios relative to catalysts prepared according to conventional methods.
[0027] Therefore, one aspect of the present disclosure is a water-gas shift reaction catalyst composition. The catalyst composition comprises zinc, present in the composition in an amount in the range of 20 wt % to 70 wt %; aluminum, present in the composition in an amount in the range of 5 wt % to 40 wt %; oxygen, present in the composition in an amount in the range of 15 wt % to 50 wt %; and one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, the one or more promoters being present in the composition in a total amount in the range of 0.1 wt % to 25 wt %, for example, in the range of 0.1 wt % to 20 wt %.
[0028] The inventors of the present application have determined that even in the absence of chromium (and, in some embodiments, even in the absence of iron), spinel-based structures can advantageously provide good catalytic activity. In certain embodiments of the compositions described herein, at least a portion of the aluminum, zinc and / or one or more promoters of the composition form a spinel structure with at least a portion of the oxygen of the composition. In certain such embodiments, the aluminum, zinc and / or one or more promoters occupy tetrahedral and / or octahedral positions of the face-centered cubic array of oxygen. Those of ordinary skill in the art will appreciate that, although in ordinary spinel structures, trivalent ions occupy octahedral positions and divalent ions occupy tetrahedral positions, spinel structures typically also include trivalent ions occupying octahedral and / or tetrahedral positions and divalent ions occupying octahedral and / or tetrahedral positions. For example, those of ordinary skill in the art will appreciate that in an inverse spinel structure, divalent ions occupy octahedral positions and trivalent ions occupy both octahedral and tetrahedral positions.
[0029] In certain embodiments described herein, at least a portion of the zinc of the composition forms an oxide with at least a portion of the oxygen of the composition. For example, in certain embodiments described herein, at least 80% by weight (e.g., at least 85% by weight, or at least 90% by weight) of the catalyst composition comprises zinc oxide and a crystalline spinel material having such a structure, wherein one or more promoters, aluminum and / or zinc occupy tetrahedral and / or octahedral positions of a face-centered cubic array of oxygen. For example, in some embodiments, at least 95% by weight (e.g., at least 97.5% by weight, or at least 99% by weight) of the catalyst composition comprises zinc oxide and the crystalline spinel material. In certain such embodiments, at least 50% by weight (e.g., at least 60% by weight, or at least 70% by weight) of the catalyst composition is the crystalline spinel material.
[0030] It is noteworthy that the promoter can become part of the spinel structure. Advantageously, the inventors of the present application have determined that incorporating at least a portion of the promoter into the spinel structure can provide improved catalyst activity. Without being bound by theory, the improvement can be attributed to the defects and deformations introduced into the spinel structure when incorporating one or more promoters, as indicated by the evidence of unit cell expansion and lack of additional phases from the promoter. Therefore, in certain embodiments, the material of the present disclosure does not include a promoter-containing phase (e.g., selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, as described below) in an amount exceeding 5% (e.g., exceeding 2% or exceeding 0.1%) of the material. For example, in certain embodiments of the composition described herein in addition, the material is substantially free of a promoter-containing phase separated from the spinel structure.
[0031] In certain embodiments described herein, the crystalline spinel unit cell has a size of at least 8.1 Å (e.g., ZnAl2O4 type or ZnFe 1.5 Al 0.5 In certain embodiments, the crystallized spinel unit cell has a size of at least 8.125 Å, or at least 8.15 Å, or at least 8.175 Å, or at least 8.2 Å, or at least 8.225 Å, or at least 8.25 Å. As will be appreciated by one of ordinary skill in the art, crystal size can be determined using X-ray crystallography.
[0032] As noted above, zinc is present in the composition in an amount in the range of 20 wt % to 70 wt %. The amount of zinc in the catalyst composition of the present disclosure may vary within this range. For example, in certain embodiments described in addition herein, zinc is present in the composition in an amount in the range of 25 wt % to 70 wt %, for example, 30 wt % to 70 wt %, or 35 wt % to 70 wt %, or 40 wt % to 70 wt %, or 50 wt % to 70 wt %. In certain embodiments described in addition herein, zinc is present in the composition in an amount in the range of 20 wt % to 65 wt %, for example, 25 wt % to 65 wt %, or 30 wt % to 65 wt %, or 35 wt % to 65 wt %, or 40 wt % to 65 wt %, or 50 wt % to 65 wt %. In some embodiments described in addition herein, zinc is present in the composition in an amount in the range of 20% to 60% by weight, for example, 25% to 60% by weight, or 30% to 60% by weight, or 35% to 60% by weight, or 40% to 60% by weight, or 45% to 60% by weight. In some embodiments described in addition herein, zinc is present in the composition in an amount in the range of 20% to 55% by weight, for example, 25% to 55% by weight, or 30% to 55% by weight, or 35% to 55% by weight, or 40% to 55% by weight. In some embodiments described in addition herein, zinc is present in the composition in an amount in the range of 20% to 50% by weight, for example, 25% to 50% by weight, or 30% to 50% by weight, or 35% to 50% by weight. Zinc is calculated as elemental zinc on the basis of calcination. It is contemplated that an amount of zinc in this paragraph can be combined with any amount of aluminum, any amount of oxygen, and any amount(s) of promoter(s) described elsewhere herein.
[0033] As noted above, aluminum is present in the composition in an amount in the range of 5% by weight to 40% by weight. As with zinc, the amount of aluminum in the composition of the present disclosure can be varied. In certain embodiments described in addition herein, aluminum is present in the composition in an amount in the range of 10% by weight to 40% by weight, for example, 15% by weight to 40% by weight, or 20% by weight to 40% by weight, or 25% by weight to 40% by weight, or 30% by weight to 40% by weight. In certain embodiments described in addition herein, aluminum is present in the composition in an amount in the range of 5% by weight to 35% by weight, for example, 10% by weight to 35% by weight, or 15% by weight to 35% by weight, or 20% by weight to 35% by weight, or 25% by weight to 35% by weight. In certain embodiments described in addition herein, aluminum is present in the composition in an amount in the range of 5% by weight to 30% by weight, for example, 10% by weight to 30% by weight, or 15% by weight to 30% by weight, or 20% by weight to 30% by weight. In certain embodiments described herein, aluminum is present in the composition in an amount ranging from 5% to 25% by weight, e.g., from 10% to 25% by weight, or from 15% to 25% by weight. In certain embodiments described herein, aluminum is present in the composition in an amount ranging from 5% to 20% by weight, e.g., from 10% to 20% by weight, or from 5% to 15% by weight. Aluminum is calculated as elemental aluminum on a calcined basis. It is contemplated that an amount of aluminum in this paragraph may be combined with any amount of zinc, any amount of oxygen, and any amount of promoter (s) described elsewhere herein.
[0034] As noted above, oxygen is present in the composition in an amount in the range of 15% by weight to 50% by weight. The amount of oxygen in the composition described herein may also be changed. Oxygen is desirably present in the composition in an amount sufficient to balance the charge, although in some embodiments there may be a small amount (desirably less than 1% by weight) of other forms of anionic materials (e.g., halide) to balance the charge. In certain embodiments described in addition herein, oxygen is present in an amount in the range of 20% by weight to 50% by weight, for example, 25% by weight to 50% by weight, or 30% by weight to 50% by weight, or 35% by weight to 50% by weight, or 40% by weight to 50% by weight. In certain embodiments described in addition herein, oxygen is present in an amount in the range of 20% by weight to 45% by weight, for example, 25% by weight to 45% by weight, or 30% by weight to 45% by weight, or 35% by weight to 45% by weight. In certain embodiments described herein, oxygen is present in an amount in the range of 20% to 40% by weight, e.g., 25% to 40% by weight, or 30% to 40% by weight. In certain embodiments described herein, oxygen is present in an amount in the range of 20% to 35% by weight, e.g., 25% to 35% by weight, or 20% to 30% by weight. Oxygen is calculated as elemental aluminum on a calcined basis.
[0035] As described above, the catalyst composition comprises a total amount of one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon in the range of 0.1 wt % to 25 wt % (i.e., calculated on the basis of the calcined elements). In certain embodiments of the composition described in addition herein, the composition comprises only one promoter selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon. One or more appropriate promoters will be selected based on the description herein by a person of ordinary skill in the art. For example, in certain embodiments of the composition described in addition herein, the composition comprises one or more (e.g., one) promoters selected from vanadium, magnesium, copper, cobalt and iron. In another example, in certain embodiments of the composition described in addition herein, the composition comprises one or more (e.g., one) promoters selected from vanadium, magnesium, copper and cobalt. In yet another example, in certain embodiments of the composition described in addition herein, the composition comprises one or more (e.g., one) promoters selected from vanadium, cobalt and iron. In certain embodiments of the compositions otherwise described herein, the composition comprises a first promoter selected from vanadium, magnesium, copper, cobalt, and iron (e.g., selected from vanadium, magnesium, copper, and cobalt; or selected from vanadium, cobalt, and iron) and a second promoter selected from vanadium, magnesium, copper, cobalt, and iron. For example, in certain such embodiments, the composition comprises a first promoter selected from vanadium and magnesium, and copper as a second promoter.
[0036] As described above, the total amount of the promoter in the composition is in the range of 0.1 wt % to 25 wt %. For example, in some embodiments of the composition described in addition herein, one or more promoters are present in a total amount in the range of 0.5 wt % to 25 wt %, or 1 wt % to 25 wt %, or 5 wt % to 25 wt %, or 10 wt % to 25 wt %. In some embodiments of the composition described in addition herein, one or more promoters are present in a total amount in the range of 0.1 wt % to 20 wt %, for example, 0.5 wt % to 20 wt %, or 1 wt % to 20 wt %, or 2 wt % to 20 wt %, or 3 wt % to 20 wt %, or 5 wt % to 20 wt %, or 7 wt % to 20 wt %, or 10 wt % to 20 wt %, or 15 wt % to 20 wt %. In certain embodiments of the compositions described herein, one or more promoters are present in a total amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In certain embodiments of the compositions described herein, one or more promoters are present in a total amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In certain embodiments of the compositions described herein, one or more promoters are present in a total amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, one or more promoters are present in a total amount in the range of 0.1 wt % to 5 wt %, e.g., 0.5 wt % to 5 wt %, or 1 wt % to 5 wt %, or 2 wt % to 5 wt %. All amounts of promoters described herein are calculated on an elemental, calcined basis. When multiple promoters are present, their total amount can be selected to fall within the range described above.
[0037] In certain embodiments of the compositions described herein, copper is present in the composition in an amount in the range of, for example, 0.1% to 25% by weight. For example, in certain embodiments of the compositions described herein, copper is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In certain embodiments of the compositions described herein, copper is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, copper is present in an amount ranging from 0.1% to 15% by weight, for example, from 0.5% to 15% by weight, or from 1% to 15% by weight, or from 2% to 15% by weight, or from 3% to 15% by weight, or from 5% to 15% by weight, or from 7% to 15% by weight. In certain embodiments of the compositions described herein, copper is present in an amount ranging from 0.1% to 10% by weight, for example, from 0.5% to 10% by weight, or from 1% to 10% by weight, or from 2% to 10% by weight, or from 3% to 10% by weight, or from 5% to 10% by weight. In certain embodiments of the compositions described herein, copper is present in an amount ranging from 0.1% to 7% by weight, for example, from 0.5% to 7% by weight, or from 1% to 7% by weight, or from 2% to 7% by weight, or from 3% to 7% by weight. In certain embodiments of the compositions otherwise described herein, copper is present in an amount ranging from 0.1 wt % to 5 wt %, e.g., 0.5 wt % to 5 wt %, or 1 wt % to 5 wt %, or 2 wt % to 5 wt %. However, in other embodiments, copper is not present in the composition.
[0038] In certain copper-containing embodiments described herein, an additional promoter, for example selected from vanadium and magnesium, is further present in the composition in an amount in the range of 0.1 wt % to 20 wt %, for example, 0.5 wt % to 17.5 wt %, or 1 wt % to 15 wt %, or in any other range described below,
[0039] In some embodiments of the compositions described herein, vanadium is present in the composition in an amount in the range of, for example, 0.1% to 25% by weight. For example, in some embodiments of the compositions described herein, vanadium is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In some embodiments of the compositions described herein, vanadium is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, vanadium is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In certain embodiments of the compositions described herein, vanadium is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In certain embodiments of the compositions described herein, vanadium is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, vanadium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, vanadium is not present in the composition.
[0040] In some embodiments of the compositions described herein, magnesium is present in the composition in an amount in the range of, for example, 0.1% to 25% by weight. For example, in some embodiments of the compositions described herein, magnesium is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In some embodiments of the compositions described herein, magnesium is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, magnesium is present in an amount ranging from 0.1% to 15% by weight, for example, from 0.5% to 15% by weight, or from 1% to 15% by weight, or from 2% to 15% by weight, or from 3% to 15% by weight, or from 5% to 15% by weight, or from 7% to 15% by weight. In certain embodiments of the compositions described herein, magnesium is present in an amount ranging from 0.1% to 10% by weight, for example, from 0.5% to 10% by weight, or from 1% to 10% by weight, or from 2% to 10% by weight, or from 3% to 10% by weight, or from 5% to 10% by weight. In certain embodiments of the compositions described herein, magnesium is present in an amount ranging from 0.1% to 7% by weight, for example, from 0.5% to 7% by weight, or from 1% to 7% by weight, or from 2% to 7% by weight, or from 3% to 7% by weight. In certain embodiments of the compositions otherwise described herein, magnesium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, magnesium is not present in the composition.
[0041] In certain embodiments of the compositions described herein, cobalt is present in the composition in an amount in the range of, for example, 0.1% to 25% by weight. For example, in certain embodiments of the compositions described herein, cobalt is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In certain embodiments of the compositions described herein, cobalt is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, cobalt is present in an amount ranging from 0.1% to 15% by weight, for example, from 0.5% to 15% by weight, or from 1% to 15% by weight, or from 2% to 15% by weight, or from 3% to 15% by weight, or from 5% to 15% by weight, or from 7% to 15% by weight. In certain embodiments of the compositions described herein, cobalt is present in an amount ranging from 0.1% to 10% by weight, for example, from 0.5% to 10% by weight, or from 1% to 10% by weight, or from 2% to 10% by weight, or from 3% to 10% by weight, or from 5% to 10% by weight. In certain embodiments of the compositions described herein, cobalt is present in an amount ranging from 0.1% to 7% by weight, for example, from 0.5% to 7% by weight, or from 1% to 7% by weight, or from 2% to 7% by weight, or from 3% to 7% by weight. In certain embodiments of the compositions otherwise described herein, cobalt is present in an amount ranging from 0.1 wt % to 5 wt %, e.g., 0.5 wt % to 5 wt %, or 1 wt % to 5 wt %, or 2 wt % to 5 wt %. However, in other embodiments, cobalt is not present in the composition.
[0042] In some embodiments of the compositions described in addition herein, iron is present in the compositions in an amount in the range of, for example, 0.1% by weight to 25% by weight. For example, in some embodiments of the compositions described in addition herein, iron is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In some embodiments of the compositions described in addition herein, iron is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In some embodiments of the compositions described herein in addition, iron is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In some embodiments of the compositions described herein in addition, iron is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In some embodiments of the compositions described herein in addition, iron is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, iron is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, iron is not present in the composition.
[0043] In some embodiments of the compositions described in addition herein, cerium is present in the compositions in an amount in the range of, for example, 0.1% by weight to 25% by weight. For example, in some embodiments of the compositions described in addition herein, cerium is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In some embodiments of the compositions described in addition herein, cerium is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In some embodiments of the compositions described herein, cerium is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In some embodiments of the compositions described herein, cerium is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In some embodiments of the compositions described herein, cerium is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, cerium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, cerium is not present in the composition.
[0044] In some embodiments of the compositions described in addition herein, manganese is present in the compositions in an amount in the range of, for example, 0.1% by weight to 25% by weight. For example, in some embodiments of the compositions described in addition herein, manganese is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In some embodiments of the compositions described in addition herein, manganese is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In some embodiments of the compositions described herein, manganese is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In some embodiments of the compositions described herein, manganese is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In some embodiments of the compositions described herein, manganese is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, manganese is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, manganese is not present in the composition.
[0045] In some embodiments of the compositions described in addition herein, calcium is present in the compositions in an amount in the range of, for example, 0.1% by weight to 25% by weight. For example, in some embodiments of the compositions described in addition herein, calcium is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In some embodiments of the compositions described in addition herein, calcium is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In some embodiments of the compositions described herein, calcium is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In some embodiments of the compositions described herein, calcium is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In some embodiments of the compositions described herein, calcium is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, calcium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. Calcium may be present in the composition as a component of crystalline spinel, and / or as part of a separate calcium-containing phase, as described below. However, in other embodiments, calcium is not present in the composition.
[0046] In certain embodiments of the compositions described herein, silicon is present in the composition in an amount in the range of, for example, 0.1% to 20% by weight. For example, in certain embodiments of the compositions described herein, silicon is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In certain embodiments of the compositions described herein, silicon is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, silicon is present in an amount ranging from 0.1% to 15% by weight, for example, from 0.5% to 15% by weight, or from 1% to 15% by weight, or from 2% to 15% by weight, or from 3% to 15% by weight, or from 5% to 15% by weight, or from 7% to 15% by weight. In certain embodiments of the compositions described herein, silicon is present in an amount ranging from 0.1% to 10% by weight, for example, from 0.5% to 10% by weight, or from 1% to 10% by weight, or from 2% to 10% by weight, or from 3% to 10% by weight, or from 5% to 10% by weight. In certain embodiments of the compositions described herein, silicon is present in an amount ranging from 0.1% to 7% by weight, for example, from 0.5% to 7% by weight, or from 1% to 7% by weight, or from 2% to 7% by weight, or from 3% to 7% by weight. In certain embodiments of the compositions described herein, silicon is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, silicon is not present in the composition.
[0047] In some embodiments of the compositions described herein, nickel is present in the composition in an amount in the range of, for example, 0.1% to 20% by weight. For example, in some embodiments of the compositions described herein, nickel is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In some embodiments of the compositions described herein, nickel is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, nickel is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In certain embodiments of the compositions described herein, nickel is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In certain embodiments of the compositions described herein, nickel is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, nickel is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, nickel is not present in the composition.
[0048] In some embodiments of the compositions described herein in addition, boron is present in the compositions in an amount in the range of, for example, 0.1% by weight to 20% by weight. For example, in some embodiments of the compositions described herein in addition, boron is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In some embodiments of the compositions described herein in addition, boron is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In certain embodiments of the compositions described herein, boron is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In certain embodiments of the compositions described herein, boron is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In certain embodiments of the compositions described herein, boron is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, boron is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, boron is not present in the composition.
[0049] In certain embodiments of the compositions described herein, zirconium is present in the composition in an amount in the range of, for example, 0.1% to 20% by weight. For example, in certain embodiments of the compositions described herein, zirconium is present in an amount in the range of 0.5% to 25% by weight, or 1% to 25% by weight, or 5% to 25% by weight, or 10% to 25% by weight. In certain embodiments of the compositions described herein, zirconium is present in an amount in the range of 0.1% to 20% by weight, for example, 0.5% to 20% by weight, or 1% to 20% by weight, or 2% to 20% by weight, or 3% to 20% by weight, or 5% to 20% by weight, or 7% to 20% by weight, or 10% to 20% by weight, or 15% to 20% by weight. In certain embodiments of the compositions described herein, zirconium is present in an amount in the range of 0.1% to 15% by weight, for example, 0.5% to 15% by weight, or 1% to 15% by weight, or 2% to 15% by weight, or 3% to 15% by weight, or 5% to 15% by weight, or 7% to 15% by weight. In certain embodiments of the compositions described herein, zirconium is present in an amount in the range of 0.1% to 10% by weight, for example, 0.5% to 10% by weight, or 1% to 10% by weight, or 2% to 10% by weight, or 3% to 10% by weight, or 5% to 10% by weight. In certain embodiments of the compositions described herein, zirconium is present in an amount in the range of 0.1% to 7% by weight, for example, 0.5% to 7% by weight, or 1% to 7% by weight, or 2% to 7% by weight, or 3% to 7% by weight. In certain embodiments of the compositions described herein, zirconium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. However, in other embodiments, zirconium is not present in the composition.
[0050] In certain embodiments of the compositions described herein in addition, potassium is present in the composition in an amount in the range of, for example, 0.1% by weight to 20% by weight. For example, in certain embodiments of the compositions described herein in addition, potassium is present in an amount in the range of 0.5% by weight to 25% by weight, or 1% by weight to 25% by weight, or 5% by weight to 25% by weight, or 10% by weight to 25% by weight. In certain embodiments of the compositions described herein in addition, potassium is present in an amount in the range of 0.1% by weight to 20% by weight, for example, 0.5% by weight to 20% by weight, or 1% by weight to 20% by weight, or 2% by weight to 20% by weight, or 3% by weight to 20% by weight, or 5% by weight to 20% by weight, or 7% by weight to 20% by weight, or 10% by weight to 20% by weight, or 15% by weight to 20% by weight. In certain embodiments of the compositions described herein, potassium is present in an amount ranging from 0.1% to 15% by weight, for example, from 0.5% to 15% by weight, or from 1% to 15% by weight, or from 2% to 15% by weight, or from 3% to 15% by weight, or from 5% to 15% by weight, or from 7% to 15% by weight. In certain embodiments of the compositions described herein, potassium is present in an amount ranging from 0.1% to 10% by weight, for example, from 0.5% to 10% by weight, or from 1% to 10% by weight, or from 2% to 10% by weight, or from 3% to 10% by weight, or from 5% to 10% by weight. In certain embodiments of the compositions described herein, potassium is present in an amount ranging from 0.1% to 7% by weight, for example, from 0.5% to 7% by weight, or from 1% to 7% by weight, or from 2% to 7% by weight, or from 3% to 7% by weight. In certain embodiments of the compositions described herein, potassium is present in an amount ranging from 0.1% to 5% by weight, e.g., from 0.5% to 5% by weight, or from 1% to 5% by weight, or from 2% to 5% by weight. Potassium may be present in the composition as a component of the crystalline spinel, and / or as a separate potassium-containing phase, as described below. However, in other embodiments, potassium is not present in the composition.
[0051] Since zinc aluminum spinel itself generally has an idealized chemical formula of ZnAl2O4, it is desirable to select a ratio of zinc to aluminum that, along with the other elemental components, provides a desired amount of spinel structure. In some embodiments of the compositions otherwise described herein, the composition comprises zinc and aluminum oxide in an atomic molar ratio (i.e., Zn:Al) in the range of 0.5:2 to 4:2. For example, in certain embodiments of the compositions otherwise described herein, the composition comprises an atomic molar ratio of between 0.75:2 and 4:2, or 1:2 and 4:2, or 1.25:2 and 4:2, or 1.5:2 and 4:2, or 1.75:2 and 4:2, or 2:2 and 4:2, or 2.25:2 and 4:2, or 2.5:2 and 4:2, or 2.75:2 and 4:2, or 3:2 and 4:2, or 0.5:2 and 3.75:2, or 0.5:2 and 3.5:2, or 0.5:2 and 3.25:2, or 0.5:2 and 3:2, or 0.5:2 and 2.75:2. In some embodiments, the composition has a zinc / alumina atomic ratio of at least 0.75:2, or at least 0.9:2. In certain such embodiments, the composition has a zinc to alumina ratio of no greater than 2:2.
[0052] In some embodiments of the compositions otherwise described herein, the composition comprises zinc and one or more promoters (e.g., vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and / or silicon), and the total atomic molar ratio of promoter to zinc (i.e., promoter:Zn) is in the range of 0.001:1 to 0.5:1. For example, in certain embodiments of the compositions otherwise described herein, the composition comprises zinc and one or more promoters, and the total atomic molar ratio of promoter to zinc is between 0.005:1 and 0.5:1, or 0.01:1 and 0.5:1, or 0.025:1 and 0.5:1, or 0.05:1 and 0.5:1, or 0.075:1 and 0.5:1, or 0.1:1 and 0.5:1, or 0.125:1 and 0.5:1, or 0.15:1 and 0.5:1, or 0.175:1 and 0.5:1, or 0.2:1 and 0.5:1, or 0.25:1 and 0.5:1, or 0.3:1 and 0.5:1, or 0.35:1 and 0.5:1, or 0.4:1 and 0.5:1. , or 0.001:1 to 0.45:1, or 0.001:1 to 0.4:1, or 0.001:1 to 0.35:1, or 0.001:1 to 0.3:1, or 0.001:1 to 0.25:1, or 0.001:1 to 0.2:1, or 0.001:1 to 0.175:1, or 0.001:1 to 0.15 :1, or 0.001:1 to 0.125, or 0.001:1 to 0.1, or 0.001:1 to 0.075, or 0.001:1 to 0.05:1, or 0.005:1 to 0.4:1, or 0.01:1 to 0.3.5:1, or 0.02:1 to 0.3:1, or 0.05:1 to 0.2:1.
[0053] In various embodiments of the composition described in addition herein, the composition may further comprise one or more alkali metals and / or alkaline earth metals that are not part of the crystalline spinel. For example, in certain such embodiments, the composition comprises one or more of potassium, sodium, magnesium, calcium, rubidium and cesium that are not part of the crystalline spinel. The alkali metal and / or alkaline earth metal may be provided (e.g., via impregnation) as any compound (e.g., as an oxide) that additionally provides the metal to the calcined catalyst composition (e.g., before the calcination step). For example, in certain embodiments, the alkali metal and / or alkaline earth metal is provided as a salt selected from carbonates, nitrates, acetates, formates, oxalates, molybdates and citrates, and in certain embodiments described in addition herein, potassium is provided as a salt, such as potassium carbonate, which is introduced via impregnation before the calcination step. The calcination may be the same calcination step used to form the spinel, or a subsequent additional calcination step. Typically, such alkali metals and alkaline earth metals may be present in the calcined composition in the form of oxides separated from the crystalline spinel structure. Thus, in certain embodiments, the only phases substantially present (e.g., in an amount greater than 2%, 1%, or 0.5%) other than the crystalline spinel and zinc oxide phases are phases containing one or more alkali metals and / or alkaline earth metals, e.g., in the form of oxides.
[0054] In certain embodiments of the compositions described herein, the composition comprises potassium (e.g., in the form of an oxide), other than any potassium in the crystalline spinel, in an amount ranging from 0.01% to 5% by weight. For example, in certain embodiments of the compositions described herein, the composition comprises a potassium source in an amount ranging from 0.01% to 3% by weight, or from 0.01% to 2% by weight, or from 0.1% to 5% by weight, or from 0.1% to 3% by weight, or from 0.1% to 2% by weight, or from 0.5% to 5% by weight, or from 0.5% to 3% by weight, or from 0.5% to 2% by weight, or from 1% to 5% by weight, or from 1% to 3% by weight, calculated as elemental potassium on a calcined basis.
[0055] One of ordinary skill in the art will understand that, unless otherwise indicated, the amounts of material in the calcined catalyst composition should be calculated on an as-calcined basis, exclusive of any organic material and any absorbed water.
[0056] In certain embodiments, the composition described herein further comprises 0.25% to 3% by weight of potassium (e.g., as an oxide); 30% to 60% by weight of zinc, 10% to 35% by weight of aluminum, and 1% to 15% by weight of a first promoter (e.g., selected from vanadium, magnesium, copper, cobalt, and iron). In certain embodiments, the composition described herein further comprises 0.25% to 3% by weight of potassium (e.g., as an oxide); 30% to 60% by weight of zinc, 10% to 35% by weight of aluminum, and 5% to 15% by weight of a first promoter (e.g., selected from vanadium, magnesium, copper, and cobalt; or selected from vanadium, cobalt, and iron). In certain such embodiments, the composition further comprises 1% to 15% by weight of a second promoter (e.g., selected from vanadium, magnesium, copper, cobalt, and iron) calculated on an elemental, calcined basis. For example, in certain embodiments described herein further, the first promoter is selected from vanadium and magnesium and the second promoter is copper.
[0057] Those of ordinary skill in the art will appreciate that other components may be present in the compositions described herein. However, in certain desirable embodiments of the compositions described herein, the compositions do not include more than 1% by weight of chromium, preferably do not include more than 0.5% by weight, more than 0.1% by weight, more than 0.05% by weight, or more than (less than) 0.01% by weight of chromium. Similarly, in certain embodiments of the compositions described herein, the compositions do not include more than 1% by weight of iron, for example, do not include more than 0.5% by weight, more than 0.1% by weight, more than 0.05% by weight, or more than (less than) 0.01% by weight of iron. In certain embodiments of the compositions described herein, the compositions (comprising) do not include more than 1% by weight (for example, do not include more than 0.5% by weight, more than 0.1% by weight, more than 0.05% by weight, or more than (less than) 0.01% by weight) of each of the non-cerium lanthanides. In certain embodiments of the compositions described herein, the composition does not include more than 1% by weight (e.g., does not include more than 0.5%, more than 0.1%, more than 0.05%, or even more than 0.01%) of each of the transition metals other than vanadium, manganese, copper, cobalt, and iron. In certain embodiments of the compositions described herein, the composition does not include more than 1% by weight (e.g., more than 0.5%, more than 0.1%, more than 0.05%, or even more than 0.01%) of elements other than zinc, aluminum, oxygen, carbon, halogens, potassium, and one or more promoters.
[0058] In certain desirable embodiments of the compositions otherwise described herein, the total amount of one or more promoters (e.g., vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium, and silicon), aluminum, zinc, oxygen, and alkali and / or alkaline earth metals is at least 80 weight percent, or at least 85 weight percent, or at least 90 weight percent, or at least 95 weight percent, or at least 97.5 weight percent, or at least 99 weight percent of the composition.
[0059] In certain such embodiments of the compositions described herein in addition, at least a portion of the potassium contained in the composition is located on the surface of such a crystalline spinel material, which comprises one or more promoters, aluminum and / or zinc occupying tetrahedral and / or octahedral positions of a face-centered cubic array of oxygen. Such a material can be prepared, for example, by first preparing a crystalline spinel material (e.g., by calcining a spinel precursor described herein), and then impregnating the material with a potassium source. One of ordinary skill in the art will understand that substances "located on the surface" include substances that are chemically bound to atoms of the surface and substances that are themselves part of the surface (e.g., by exchanging with surface atoms, embedding, etc.). Substances "located on the surface" have a significantly higher concentration (e.g., at least 100% higher) on the surface of the material (including the surface of the internal pores) than in the interior of the material. One of ordinary skill in the art will further understand that the "surface" of the composition is not only composed of the outermost atoms of the composition, but includes, for example, the outermost 50 nm, 100 nm, 250 nm, 500 nm, 750 nm or even 1 μm of the composition.
[0060] The catalyst composition desirably comprises a crystalline spinel material in the form of small crystallites. In some such embodiments of the composition described in addition herein, at least 90% by weight of the crystalline spinel material is present in the composition as a crystallite with a major dimension less than 500 nm. For example, in some embodiments of the composition described in addition herein, at least 95% by weight of the crystalline spinel material, or at least 97.5% by weight or at least 99% by weight are present in the composition as a crystallite with a major dimension less than 500 nm, or less than 400 nm, or less than 300 nm, or less than 200 nm, or less than 100 nm, or less than 75 nm, or less than 50 nm, or less than 25 nm. Crystallite can exist as an agglomerate of a single crystal; Such an agglomerate can have a larger particle size.
[0061] In certain embodiments described herein, the catalyst composition (eg, comprising the crystalline spinel material in the form of small crystallites) has at least 20 m 2 / g surface area. For example, in certain such embodiments, the surface area of the catalyst composition is 20 m2 / g to 300 m 2 / g, or 20 m 2 / g to 250 m 2 / g, or 20 m 2 / g to 200 m 2 / g, or 20m 2 / g to 150 m 2 / g, or 20 m 2 / g to 100 m 2 / g, or 20 m 2 / g to 75 m 2 / g, or 50 m 2 / g to 300 m 2 / g, or 75m 2 / g to 300 m 2 / g, or 100 m 2 / g to 300 m 2 / g, or 150 m 2 / g to 300 m 2 / g, or 200 m 2 / g to 300 m 2 / g, or 250 m 2 / g to 300 m 2 / g, or 25 m 2 / g to 125 m 2 / g, or 75 m 2 / g to 175 m 2 / g, or 125 m 2 / g to 225 m 2 / g range.
[0062] As will be understood by those of ordinary skill in the art and described in more detail below, the compositions of the present disclosure may be prepared in a variety of ways. In certain desired embodiments, the compositions described herein in addition are in the form of a calcined precipitate. For example, in some embodiments of the compositions of the present disclosure, the catalyst composition comprises a crystalline spinel material that is a calcined product of a precipitation product of a solution of zinc ions, aluminum ions, one or more promoters (e.g., vanadium, magnesium, manganese, cerium, copper, cobalt, calcium, nickel, boron, zirconium, potassium and / or silicon) ions and hydroxide ions (e.g., layered double hydroxides or oxy-hydride materials). In certain such embodiments of the compositions described herein in addition, the catalyst composition comprises a calcined product of a crystalline spinel material impregnated with a potassium source.
[0063] Another aspect of the present disclosure is a method for preparing a water-gas shift reaction catalyst composition. The method includes providing a spinel precursor comprising zinc, aluminum, oxygen and one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, and then calcining the spinel precursor. The catalyst composition comprises zinc, calculated on an elemental, calcined basis, present in the material in an amount ranging from 20 wt % to 70 wt %; aluminum, present in the material in an amount ranging from 5 wt % to 40 wt %; one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon: each promoter is present in the composition in an amount ranging from 0.1 wt % to 20 wt %; and oxygen, present in the material in an amount ranging from 15 wt % to 50 wt %. The amounts and characteristics of the various components may be as described above in addition to the catalyst composition of the present disclosure. One of ordinary skill in the art can provide a spinel-type precursor suitable for providing the desired amounts of zinc, aluminum, oxygen, and one or more promoters.
[0064] As described above, in certain desired embodiments, the spinel precursor is calcined to provide the composition of the present disclosure. The spinel precursor can be any material that forms a crystalline spinel material, that is, a material having a structure in which, when calcined, one or more promoters, aluminum and / or zinc occupy tetrahedral and / or octahedral positions of a face-centered cubic array of oxygen. For example, in certain embodiments of the method described in addition herein, the spinel precursor comprises a layered double hydroxide, a hydrated oxide, a hydroxide or an amorphous material. In other embodiments of the method described in addition herein, the spinel precursor can be any of the many spinel precursors known in the art (e.g., a hydrogel). In certain embodiments of the method described in addition herein, the spinel precursor is a precipitation product of an ionic solution. For example, in certain embodiments of the method described in addition herein, the spinel precursor is a precipitation product of a solution of zinc ions, aluminum ions, one or more promoters (e.g., vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and / or silicon) ions and hydroxide ions.
[0065] In certain such embodiments of the methods otherwise described herein, such precipitation product comprises a layered double hydroxide or oxy-hydroxide structure, ie, is a layered double hydroxide or oxy-hydroxide material.
[0066] As described above, the method includes calcining the spinel precursor.In some embodiments of the methods otherwise described herein, the calcining step is performed at a temperature in the range of 200°C to 700°C. For example, in certain embodiments of the methods otherwise described herein, the calcining step is conducted at a temperature in the range of 200°C to 675°C, or 200°C to 650°C, or 200°C to 625°C, or 200°C to 600°C, or 200°C to 575°C, or 200°C to 550°C, or 225°C to 700°C, or 250°C to 700°C, or 275°C to 700°C, or 300°C to 700°C, or 325°C to 700°C, or 350°C to 700°C, or 225°C to 675°C, or 250°C to 650°C, or 275°C to 625°C, or 300°C to 600°C, or 325°C to 575°C, or 350°C to 550°C, or 400°C to 500°C.
[0067] In some embodiments of the methods described herein, the spinel precursor is calcined for a period of time in the range of 5 minutes to 12 hours. For example, in certain embodiments of the methods described herein, the spinel precursor is calcined for a period of time in the range of 10 minutes to 12 hours, or 15 minutes to 12 hours, or 20 minutes to 12 hours, or 30 minutes to 12 hours, or 45 minutes to 12 hours, or 1 hour to 12 hours, or 1.5 hours to 12 hours, or 2 hours to 12 hours, or 5 minutes to 11 hours, or 5 minutes to 10 hours, or 5 minutes to 9 hours, or 5 minutes to 8 hours, or 5 minutes to 7.5 hours, or 5 minutes to 7 hours, or 5 minutes to 6.5 hours, or 5 minutes to 6 hours, or 5 minutes to 5.5 hours, or 5 minutes to 5 hours, or 30 minutes to 11 hours, or 1 hour to 10 hours, or 1.5 hours to 9 hours, or 2 hours to 8 hours.
[0068] In some embodiments of the methods described herein, the spinel precursor is dried prior to calcination. In some embodiments of the methods described herein, the spinel precursor is dried at a temperature in the range of 40°C to 200°C. For example, in certain embodiments of the methods described herein, the spinel precursor is dried at a temperature in the range of 60°C to 200°C, or 80°C to 200°C, or 100°C to 200°C, or 40°C to 180°C, or 40°C to 160°C, or 40°C to 140°C, or 60°C to 180°C, or 80°C to 160°C, or 100°C to 140°C.
[0069] In some embodiments of the methods described herein, the spinel precursor is dried for a period of time in the range of 15 minutes to 36 hours. For example, in certain embodiments of the methods described herein, the spinel precursor is dried for a period of time in the range of 15 minutes to 30 hours, or 15 minutes to 24 hours, or 15 minutes to 22 hours, or 15 minutes to 20 hours, or 1 hour to 36 hours, or 2 hours to 36 hours, or 4 hours to 36 hours, or 8 hours to 36 hours, or 1 hour to 30 hours, or 1 hour to 24 hours, or 1 hour to 22 hours, or 1 hour to 20 hours.
[0070] In some embodiments of the methods described herein, the method for preparing a water-gas shift reaction catalyst composition further comprises providing an alkali metal and / or alkaline earth metal source to the composition. In certain such embodiments of the methods described herein, the method comprises impregnating the calcined composition with an alkali metal and / or alkaline earth metal source and calcining the impregnated composition. The calcination may be the same calcination as the calcination of the spinel, or a separate calcination. One of ordinary skill in the art will perform such impregnation using conventional methods based on the disclosure herein.
[0071] As noted above with respect to various aspects and embodiments of the catalyst compositions of the present disclosure, the alkali and / or alkaline earth metal source (e.g., potassium source) can be, for example, a carbonate, nitrate, acetate, formate, oxalate, molybdate, or citrate or any compound that provides an alkali and / or alkaline earth metal to the calcined catalyst composition. For example, in certain embodiments of the methods described further herein, the methods include impregnating the calcined composition with an aqueous solution of K2CO3, and calcining the impregnated composition.
[0072] In certain such embodiments of the methods otherwise described herein, the impregnated composition is calcined at a temperature in the range of 200°C to 700°C. For example, in certain embodiments of the methods otherwise described herein, the impregnated composition is calcined at a temperature in the range of 200°C to 675°C, or 200°C to 650°C, or 200°C to 625°C, or 200°C to 600°C, or 200°C to 575°C, or 200°C to 550°C, or 225°C to 700°C, or 250°C to 700°C, or 275°C to 700°C, or 300°C to 700°C, or 325°C to 700°C, or 350°C to 700°C, or 225°C to 675°C, or 250°C to 650°C, or 275°C to 625°C, or 300°C to 600°C, or 325°C to 575°C, or 350°C to 550°C, or 400°C to 500°C.
[0073] In some such embodiments of the methods described herein, the calcined impregnated composition is continued for a period of time in the range of 5 minutes to 12 hours. For example, in some embodiments of the methods described herein, the calcined impregnated composition is continued for a period of time in the range of 10 minutes to 12 hours, or 15 minutes to 12 hours, or 20 minutes to 12 hours, or 30 minutes to 12 hours, or 45 minutes to 12 hours, or 1 hour to 12 hours, or 1.5 hours to 12 hours, or 2 hours to 12 hours, or 5 minutes to 11 hours, or 5 minutes to 10 hours, or 5 minutes to 9 hours, or 5 minutes to 8 hours, or 5 minutes to 7.5 hours, or 5 minutes to 7 hours, or 5 minutes to 6.5 hours, or 5 minutes to 6 hours, or 5 minutes to 5.5 hours, or 5 minutes to 5 hours, or 30 minutes to 11 hours, or 1 hour to 10 hours, or 1.5 hours to 9 hours or 2 hours to 8 hours.
[0074] In certain such embodiments of the methods described herein, the impregnated composition is dried prior to calcination. In certain such embodiments of the methods described herein, the impregnated composition is dried at a temperature in the range of 40°C to 200°C. For example, in certain embodiments of the methods described herein, the spinel precursor is dried at a temperature in the range of 60°C to 200°C, or 80°C to 200°C, or 100°C to 200°C, or 40°C to 180°C, or 40°C to 160°C, or 40°C to 140°C, or 60°C to 180°C, or 80°C to 160°C, or 100°C to 140°C.
[0075] In some embodiments of the methods described herein, the impregnated composition is dried for a period of time in the range of 15 minutes to 36 hours. For example, in certain embodiments of the methods described herein, the impregnated composition is dried for a period of time in the range of 15 minutes to 30 hours, or 15 minutes to 24 hours, or 15 minutes to 22 hours, or 15 minutes to 20 hours, or 1 hour to 36 hours, or 2 hours to 36 hours, or 4 hours to 36 hours, or 8 hours to 36 hours, or 1 hour to 30 hours, or 1 hour to 24 hours, or 1 hour to 22 hours, or 1 hour to 20 hours.
[0076] Another aspect of the present disclosure is a catalyst composition prepared by the methods described herein. Advantageously, the inventors have determined that the use of such a catalyst composition can catalyze the high temperature water-gas shift reaction with comparable efficiency to conventional chromium-containing catalyst materials, and in certain embodiments, can operate over a wider range of steam to gas ratios relative to conventional catalyst materials.
[0077] The methods described herein can provide materials particularly useful for use in catalytic processes. In certain embodiments, the methods described herein provide a catalyst composition that is a calcined product of a spinel precursor comprising zinc, aluminum, oxygen, and one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium, and silicon, with an alkali or alkaline earth metal (e.g., potassium, sodium, magnesium, calcium, rubidium, and / or cesium) source optionally provided via impregnation on its surface.
[0078] The compositions described herein are particularly useful, for example, in water-gas shift reactions carried out at relatively high temperatures. As will be appreciated by those of ordinary skill in the art, the water-gas shift reaction converts water and carbon monoxide into hydrogen and carbon dioxide. Therefore, another aspect of the present disclosure is a method for carrying out such a water-gas shift reaction, the method comprising contacting a feed comprising water and carbon monoxide with a catalyst composition described herein under certain conditions to cause the formation of hydrogen and carbon dioxide. The feed can be formed, for example, by gasification of an organic feedstock (e.g., coal or biomass).
[0079] In some embodiments of the water-gas shift process described further herein, the feed comprises water and gas (i.e., comprises carbon monoxide) in a steam to gas (S / G) molar ratio of up to 1. For example, in certain such embodiments, the S / G ratio of the feed is up to 0.8, or up to 0.6, or up to 0.5, or up to 0.4, or up to 0.3, or in the range of 0.2 to 1, or 0.4 to 1, or 0.5 to 1, or 0.6 to 1, or 0.7 to 1, or 0.1 to 0.6, or 0.2 to 0.7, or 0.3 to 0.8, or 0.4 to 0.9.
[0080] In some such embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon monoxide in an amount in the range of 5 wt % to 25 wt %. For example, in some embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon monoxide in an amount in the range of 5 wt % to 20 wt %, or 5 wt % to 15 wt %, or 10 wt % to 25 wt %, or 15 wt % to 25 wt %, or 10 wt % to 20 wt %, or 10 wt % to 15 wt %. In some embodiments of the hydrogen formation method described in addition herein, the feed comprises hydrogen. In some embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon dioxide and / or nitrogen.
[0081] The contact of the feed described herein with the catalyst composition can be carried out in various ways familiar to those of ordinary skill in the art. Conventional equipment and methods can be used together with the catalyst composition of the present disclosure to provide beneficial performance. Therefore, the catalyst can be contained in a bed in a reactor vessel or divided into multiple beds in a reactor. The reaction system can contain one or more reaction vessels in series. The feed to the reaction zone can flow vertically upward in a typical plug flow reactor, or downward through a catalyst bed, or horizontally through a catalyst bed in a radial flow reactor.
[0082] The catalyst compositions described herein are desirably in a substantially reduced form. Thus, it may be desirable to treat the catalyst composition with hydrogen, for example, prior to contacting the catalyst composition with the feed. Such treatment may be performed as follows: at a temperature in the range of, for example, 250° C. to 400° C., at a temperature of, for example, 10,000 h. -1 Up to 30000 h -1 In the range (e.g. 12000 h -1 Up to 24000 h -1 The method is performed in flowing hydrogen at a GHSV in the range of 1 to 2 bar, at a pressure in the range of 2 bar to 16 bar, for at least 4 hours, for example, for a time in the range of 8 hours to 24 hours.
[0083] The contacting of the feed with the catalyst composition can be carried out using conventional methods. For example, the feed can be introduced into a reaction zone containing the catalyst composition at a constant rate, or alternatively, at a variable rate. The hydrogen formation can be carried out under gas phase conditions.
[0084] In some embodiments of the hydrogen formation methods otherwise described herein, at 10000 h -1 Up to 30000 h -1 The feed is contacted with a provided catalyst composition at a gas hourly space velocity in the range of 1000 h / min to 2000 h / min. For example, in certain embodiments of the hydrogen formation methods described elsewhere herein, at 12000 h / min -1 Up to 30000 h -1 , or 14000 h -1 Up to 30000 h -1 , or 16000 h -1 Up to 30000 h -1 , or 10000 h -1 Up to 28000 h -1 , or 10000 h -1 Up to 26000 h -1 , or 10000 h -1 Up to 24000 h -1 , or 10000 to 22000 h -1, or 10000 h -1 Up to 20000 h -1 , or 12000 h -1 Up to 28000 h -1 , or 14000 h -1 Up to 26000 h -1 , or 16 h -1 Up to 24000 h -1 , or 16000 h -1 Up to 24000 h -1 The feed is contacted with the provided catalyst composition at a gas hourly space velocity within the range of .
[0085] In some embodiments of the hydrogen formation methods otherwise described herein, the methods are conducted at a temperature in the range of 250° C. to 550° C. For example, in certain embodiments of the hydrogen formation methods otherwise described herein, the methods are conducted at a temperature in the range of 275° C. to 550° C., or 300° C. to 550° C., or 325° C. to 550° C., or 250° C. to 525° C., or 250° C. to 500° C., or 250° C. to 475° C., or 250° C. to 450° C., or 250° C. to 425° C., or 250° C. to 400° C., or 250° C. to 375° C., or 275° C. to 500° C., or 300° C. to 475° C., or 325° C. to 450° C., or 325° C. to 425° C., or 325° C. to 400° C.
[0086] In some embodiments of the hydrogen forming methods otherwise described herein, the method is carried out at a pressure in the range of 5 barg to 40 barg. For example, in certain embodiments of the hydrogen forming methods otherwise described herein, the method is carried out at a pressure in the range of 7.5 barg to 40 barg, or 10 barg to 40 barg, or 12.5 barg to 40 barg, or 15 barg to 40 barg, or 20 barg to 40 barg, or 25 barg to 40 barg, or 5 barg to 35 barg, or 5 barg to 30 barg, or 5 barg to 25 barg, or 5 barg to 20 barg, or 5 barg to 15 barg, or 7.5 barg to 35 barg, or 10 barg to 30 barg, or 12.5 barg to 25 barg.
[0087] For example, in certain embodiments further described herein, the water-gas shift reaction is a high temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 300-450° C. In other embodiments further described herein, the water-gas shift reaction is a medium temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 220-295° C. And in other embodiments further described herein, the water-gas shift reaction is a low temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 180-220° C. Example
[0088] The following examples are illustrative of specific embodiments of the present invention and its various uses. They are presented for illustrative purposes only and are not to be construed as limiting the present invention.
[0089] Example 1. Preparation of Zn / Al catalyst
[0090] A precursor solution was prepared by mixing 4.654 mL of 4.297M Zn(NO3)2 solution, 32.329 mL of 1.361M Al(NO3)3 solution and 0.667 mL of 3M Co(NO3)2 solution and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E1.
[0091] A precursor solution was prepared by mixing 5.48 mL of 4.197M Zn(NO3)2 solution, 15.02 mL of 1.361M Al(NO3)3 solution and 8.936 g of VO(CO4) solution (5.83 wt% V) and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E2.
[0092] A precursor solution was prepared by mixing 5.48 mL of 4.197M Zn(NO3)2 solution, 17.53 mL of 1.361M Al(NO3)3 solution and 5.958 g of VO(CO4) solution (5.83 wt% V) and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E3.
[0093] A precursor solution was prepared by mixing 11.401 g of 4.197 M Zn(NO3)2 solution, 21.143 g of 1.361 M Al(NO3)3 solution, 3.797 mL of 0.79 M VO(C2O4) solution and 1.471 mL of 2.04 M Cu(NO3)2 solution and diluting to 50 mL with deionized water. An alkaline solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkaline solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E4.
[0094] A precursor solution was prepared by mixing 5.24 mL of 4.197M Zn(NO3)2 solution, 16.16 mL of 1.361M Al(NO3)3 solution, 13.92 mL of 0.79M VO(C2O4) solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E5.
[0095] A precursor solution was prepared by mixing 8.35 mL of 4.194M Zn(NO3)2 solution, 15.65 mL of 1.361M Al(NO3)3 solution, 1.35 mL of 1.5M Fe(NO3)3 solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E6.
[0096] A precursor solution was prepared by mixing 7.87 mL of 4.194M Zn(NO3)2 solution, 12.93 mL of 1.361M Al(NO3)3 solution, 2.93 mL of 1.5M Fe(NO3)3 solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E7.
[0097] A precursor solution was prepared by mixing 5.48 mL of 4.194M Zn(NO3)2 solution, 17.53 mL of 1.361M Al(NO3)3 solution, 4.54 mL of 1.5M Fe(NO3)3 solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E8.
[0098] A precursor solution was prepared by mixing 13.51 mL of 4.479M Zn(NO3)2 solution, 29.39 mL of 1.361M Al(NO3)3 solution, 1 mL of 3M Mg(NO3)2 solution and 1.98 mL of 2.04MCu(NO3)2 solution and diluting to 100 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide catalyst E9.
[0099] A precursor solution was prepared by mixing 14.4 mL of 4.203M Zn(NO3)2 solution, 29.39 mL of 1.361M Al(NO3)3 solution, and diluting to 100 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE1.
[0100] A precursor solution was prepared by mixing 6.98 mL of 4.297M Zn(NO3)2 solution, 22.04 mL of 1.361M Al(NO3)3 solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE2.
[0101] A precursor solution was prepared by mixing 5.12 mL of 4.297M Zn(NO3)2 solution, 32.33 mL of 1.361M Al(NO3)3 solution, and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE3.
[0102] A precursor solution was prepared by mixing 8.30 mL of 3.975M Zn(NO3)2 solution, 19.40 mL of 1.361M Al(NO3)3 solution, and diluting to 50 mL with deionized water. A base solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the base solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE4.
[0103] A precursor solution was prepared by mixing 8.35 mL of 4.194M Zn(NO3)2 solution, 15.65 mL of 1.361M Al(NO3)3 solution, and 0.98 mL of 2.078M Ti(OH)2[(CH3CH(O-)CO2NH4]2, and diluted to 50 mL with deionized water. A base solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the base solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE5.
[0104] A precursor solution was prepared by mixing 3.95 mL of 4.053M Zn(NO3)2 solution, 11.02 mL of 1.361M Al(NO3)3 solution, 16.67 mL of 1.5M Fe(NO3)3 solution and diluting to 50 mL with deionized water. An alkali solution was prepared by mixing 100 mL of 10% KOH solution and 400 mL of 25% K2CO3 solution. The precursor solution and the alkali solution were mixed together at 60°C to cause a precipitate to form. The stirred suspension was heated to 60°C for 30 min. The precipitate was filtered and washed with deionized water and dried at 105°C. The dried filter cake was calcined at 450°C for 2 hours. The resulting powder was impregnated with an aqueous solution of K2CO3, dried at 105°C, and calcined at 450°C for 2 hours to provide comparative catalyst CE6.
[0105] Table 1. Catalyst composition
[0106] *Calculated on a weight basis. **Calculated on an atomic mole basis. Example 2. Hydrogen formation
[0107] The catalyst prepared according to Example 1 was reduced with feed gas at 330°C at 3.4 barg for 16 hours and tested in a microreactor test unit under typical high temperature shift (HTS) conditions. -1 At a gas hourly space velocity (GHSV) of 1.5 %, a feed containing 23.2% N2, 12.8% CO, 7.8% CO2 and the balance hydrogen was passed through a catalyst bed together with water in an amount providing a steam to gas (S / G) ratio of 0.6 (i.e., the molar ratio of H2O to the sum of H2, N2, CO2 and CO). The catalyst bed temperature was gradually increased from 330°C to 371°C. The catalyst was then subjected to two cycles in which the temperature of the catalyst bed was increased to 520°C and maintained for 24 h, and then decreased to 371°C and maintained for 24 h. After the temperature cycle, the S / G ratio was reduced to 0.3 and the total pressure was increased to 25 barg. The CO concentration at the reactor outlet was monitored with an online gas chromatograph (GC). In each run, a commercially available high temperature water-gas shift catalyst was used as an internal standard. The average CO conversion at 371° C. (“CO Conversion”) and the average methanol production at 371° C. and S / G=0.3 (“CH4 Production”) after two temperature cycles are provided in Table 2 below.
[0108] Table 2. Catalyst performance Example 3. X-ray diffraction
[0109] X-ray diffraction (XRD) was used to characterize the comparative catalysts CE1, CE2 and CE4 and the "used" catalysts (i.e., after hydrogen formation according to Example 2) CE1, CE6, E2, E3, E6, E7 and E8. The catalysts were calcined at 450°C before characterization. The results show that the comparative catalysts CE1, CE2, CE4 and the used catalysts CE1, E2, E3, E6, E7 and E8 contain ZnAl2O4 spinel and ZnO (see Table 3 below). In contrast, the used catalyst CE6 contains mainly aluminum-substituted zinc iron oxide (ZnFe 1.5 Al 0.5 O4) and trace amounts of hematite (Fe3O4). A representative XRD spectrum is shown in Figure 1-2 middle.
[0110] Table 3. XRD characterization data
[0111] *ZnAl2O4 spinel; **ZnFe 1.5 Al 0.5 O4 spinel
[0112] As shown in Table 3, the relative amounts of spinel and ZnO phases vary with the Zn / Al ratio (see also Table 1). Because zinc is in excess in each of comparative catalysts CE1, CE2 and CE4, the spinel unit cell size and thus the composition of the spinel does not change. Figure 1 XRD patterns of the unpromoted and vanadium promoted spent catalysts are shown. All three samples contain broad peaks associated with the spinel structure. The unit cell size of the spinel phase in the unpromoted sample (Comparative catalyst CE1) matches the literature value for ZnAl2O4 very well (a=8.0869 Å). The size of the spinel unit cell of the vanadium promoted samples (catalysts E2, E3) increases significantly with increasing vanadium content (see Table 3). Without being bound by theory, the spinel structure can be explained by the presence of Al in the crystal. 3+ and V 3+ The difference in ionic radius explains this phenomenon - when larger cations such as V 3+ Substituting Al in the octahedral B lattice of the AB2O4 spinel structure 3+ When the vanadium content is increased, the unit cell expansion may occur, causing the corresponding XRD peak to move to a lower angle. It is worth noting that the results of Example 2 show that at 371°C and S / G=0.6, the vanadium-promoted sample provides a higher CO conversion than the unpromoted comparative catalyst, and the conversion increases with the vanadium content.
[0113] A similar phenomenon was observed for the Fe-promoted catalysts. The size of the spinel unit cell of the Fe-promoted samples increased with increasing Fe content (see Table 3), indicating that Fe was incorporated into the ZnAl spinel phase (see Table 4). Figure 2 Analysis of comparative catalyst CE6 after hydrogen formation showed that the sample contained a cubic spinel phase with a large unit cell (see Table 3), which was preferably formed by aluminum-substituted zinc iron oxide (ZnFe 1.5 Al 0.5 It is noteworthy that the results of Example 2 show that at 371°C and S / G=0.6, the high iron sample undesirably provides lower CO conversion and higher methane production than the sample containing less iron.
[0114] The details shown herein are presented as examples only and for the purpose of illustrative discussion of preferred embodiments of the invention, and are presented for the purpose of providing what is believed to be the most useful and easy-to-understand description of aspects of the principles and concepts of various embodiments of the invention. In this regard, no attempt is made to show the structural details of the invention in more detail than is necessary for a basic understanding of the invention, and the description in conjunction with the accompanying drawings and / or examples makes it clear to those skilled in the art how several forms of the invention are embodied in practice. Therefore, before describing the disclosed methods and apparatus, it should be understood that the aspects described herein are not limited to specific embodiments, instruments or configurations, and therefore can certainly be changed. It should also be understood that the terms used herein are only for the purpose of describing specific aspects, and are not intended to be limiting unless expressly defined herein.
[0115] The terms "a", "an", "the" and similar references used in the context of describing the present invention (especially in the context of the claims below) should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. Recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each individual value falling within the range. Unless otherwise indicated herein, each individual value is incorporated into the specification as if it were individually recited herein. It will be further understood that the endpoints of each range are significant not only in relation to the other endpoints, but also independently of the other endpoints.
[0116] All methods described herein can be performed in the order of any suitable steps, unless otherwise indicated herein or clearly contradictory to the context. The use of any and all embodiments provided herein, or exemplary language (e.g., "such as") is intended only to better illustrate the present invention and does not set limitations on the scope of the present invention otherwise claimed. No language in the specification should be interpreted as indicating any unclaimed elements essential to the practice of the present invention.
[0117] Throughout the specification and claims, the words 'comprise,' 'comprising,' and the like are to be interpreted in an inclusive sense, as opposed to an exclusive or exhaustive sense; that is, in the sense of "including, but not limited to," unless the context clearly requires otherwise. Words using the singular or plural number also include the plural and singular, respectively. Additionally, when the words "herein," "above," and "below," and words of similar meaning, are used in this application, they shall refer to this application as a whole and not to any particular portion of this application.
[0118] As will be understood by one of ordinary skill in the art, each embodiment disclosed herein may comprise, consist essentially of, or consist of the specifically identified elements, steps, ingredients, or components thereof. As used herein, the transitional terms "comprise" or "comprises" are meant to include, but are not limited to, and permit the inclusion of unspecified elements, steps, ingredients, or components, even in large quantities. The transitional phrase "consisting of" excludes any unspecified elements, steps, ingredients, or components. The transitional phrase "consisting essentially of" limits the scope of the embodiment to the identified elements, steps, ingredients, or components and those that do not materially affect the embodiment.
[0119] Unless indicated to the contrary, the numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the desired properties sought to be obtained by the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0120] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors resulting from the standard deviation found in their respective testing measurements.
[0121] The grouping of the optional elements or embodiments of the invention disclosed herein should not be construed as limiting. Each group member may be referred to and claimed individually or in any combination with other members of the group or other elements present herein. It is expected that one or more members of the group may be included in the group, or deleted from the group, due to convenience and / or patentable reasons. When any such inclusion or deletion occurs, it is considered that the specification contains the modified group, and therefore satisfies the written description of all Markush groups used in the appended claims.
[0122] Some embodiments of the present invention are described herein, including the best mode known to the inventor for carrying out the present invention. Of course, for those skilled in the art, when reading the foregoing description, variations of the embodiments described will become clear. The inventor expects that a skilled person will adopt such variations as appropriate, and the inventor intends to practice the present invention in a manner other than the specific description herein. Therefore, the present invention includes all modifications and equivalents of the subject matter recorded in the appended claims as allowed by applicable law. In addition, the present invention includes any combination of the elements described above in all possible variants thereof, unless otherwise indicated herein or clearly contradictory to the context.
[0123] Throughout this specification, a number of patents and printed publications are cited. Each of the cited references and printed publications is incorporated herein by reference in its entirety.
[0124] In addition, it should be understood that the embodiments of the invention disclosed herein are illustrative of the principles of the present invention. Other modifications that may be adopted are within the scope of the present invention. Therefore, by way of example, but not as a limitation, alternative configurations of the present invention may be used consistent with the teachings herein. Therefore, the present invention is not limited to what is precisely shown and described.
Claims
1. A water-gas shift reaction catalyst composition comprising: zinc, present in the composition in an amount ranging from 20% to 70% by weight; aluminum, present in the composition in an amount ranging from 5 wt % to 40 wt %; one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, the one or more promoters being present in the composition in a total amount ranging from 0.1 wt % to 25 wt %; and Oxygen is present in the composition in an amount ranging from 15 wt % to 50 wt %.
2. The catalyst composition of claim 1, wherein zinc is present in an amount ranging from 25 wt% to 45 wt%.
3. The catalyst composition of claim 1, wherein aluminum is present in an amount ranging from 10 wt% to 35 wt%.
4. The catalyst composition of claim 1, wherein copper is present in an amount ranging from 0.5 wt% to 10 wt%, for example, from 1.5 wt% to 5 wt%.
5. The catalyst composition of claim 1, wherein vanadium is present in an amount ranging from 1 wt% to 15 wt%, for example, from 2 wt% to 15 wt%.
6. The catalyst composition according to any of claim 1, wherein magnesium is present in an amount ranging from 0.1 wt% to 5 wt%, for example, from 0.5 wt% to 3 wt%.
7. The catalyst composition of claim 1, wherein cobalt is present in an amount ranging from 1 wt% to 10 wt%, for example, from 2 wt% to 5 wt%.
8. The catalyst composition of claim 1, wherein iron is present in an amount ranging from 1 wt% to 15 wt%, for example, from 1.5 wt% to 10 wt%.
9. The catalyst composition of claim 1, wherein the atomic molar ratio of zinc to aluminum is in the range of 0.5:2 to 4:
2.
10. The catalyst composition of claim 1, wherein the catalyst composition comprises an alkali metal and / or alkaline earth metal that is not part of the crystalline spinel, present in the composition in an amount ranging from 0.01 wt% to 5 wt%.
11. The catalyst composition according to claim 10, wherein the alkali metal and / or alkaline earth metal is one or more of potassium, sodium, magnesium, calcium, rubidium and / or cesium, for example, potassium.
12. The catalyst composition of claim 11, wherein the only phase other than the crystalline spinel and zinc oxide phases that is substantially present (e.g., in an amount greater than 2%, 1% or 0.5%) is a phase containing one or more alkali metals and / or alkaline earth metals, e.g., in the form of oxides.
13. The catalyst composition according to claim 1, comprising: 0.25 to 3 wt % potassium; 30 to 60 wt % zinc; 10 to 35 wt % aluminum; and 1 wt % to 15 wt % of a first promoter selected from V, Mg, Cu, Co and Fe.
14. A method for preparing a water-gas shift reaction catalyst composition (e.g., according to claim 1), the method comprising: providing a spinel precursor comprising zinc; aluminum; one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon; and oxygen; and Calcination of spinel precursor, The catalyst composition comprises: zinc, present in the composition in an amount ranging from 20% to 70% by weight; aluminum, present in the composition in an amount ranging from 5 wt % to 40 wt %; one or more promoters selected from vanadium, magnesium, copper, cobalt, iron, cerium, manganese, calcium, nickel, boron, zirconium, potassium and silicon, each promoter being present in the composition in an amount ranging from 0.1 wt % to 20 wt %; and Oxygen is present in the composition in an amount ranging from 15 wt % to 50 wt %.
15. A method of performing a water gas shift reaction, the method comprising contacting a feed comprising water and carbon monoxide with the catalyst composition of claim 1 to form hydrogen and carbon dioxide.